INOVASI PEMBANGUNAN PADA KEPENGHULUAN HARAPAN MAKMUR SELATAN KECAMATAN BAGAN SINEMBAH RAYA KABUPATEN ROKAN HILIR - Aldies Eka Permata Sari; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Innovation is the great Challenge for every organization including organization of public relation service. This research is doing for having and seeing the information about innovation of construction. In the Harapan Makmur Selatan village Bagan Sinembah Raya subdistric Rokan Hilir Regency. Showing for the past growth of infrastructure construction of the village that the government doing of the Harapan Makmur Selatan village and also the writer want to knowing the innovation from the government of the village construction in Harapan Makmur Selatan Village.The concept of theory that used in this research is the innovation theory by Simonton (1994:92-94) that showed as a process, so the innovation divided by five steps, there are agenda setting, matching, redefiniting, structuring, and interconnecting. This research used cualitativ methods with investigation using data collecting observation methods, interviewa, documentation and library study that analyzed used by triangulation technic.The result of research shoes that innovation of construction in the Harapan Makmur Selatan Village Rokan Hilir regency on the process steps innovation that doing in the village are done with the best potencies in the village, example in theeducation sector is the construction of kindergarten building, in the healthy service and also in the economics village example fledgling gurame fish using traps pond in the yard beside the house and also the garden planting the commodity of fruits and vegetables that the result can be used bt the citizens and give positive influence for the village, that all not running for the village example human resources, facilities and infrastructure, fund, coordination, and new innovation in the enforcement of the village construction.Keyword : Construction, Innovation